Dominican Republic : a Caribbean crucible - Wiarda, Howard J. (Westview Press BoulderUS, 1982)
Provides an up-to-date, comprehensive overview of life in the Dominican Republic. Describes the land, people, culture, social structure, economy and political institutions and processes. Traces historical development from the Spanish conquest to the present. Discusses the role of the Dominican Republic in the international arena.